Mansfield Park [large type] - Austen, Jane, 1775-1817 (Kennebec Large Print perennial favorites collection., 2011)
In Jane Austen's third published novel after Sense and Sensibility and Pride and Prejudice, young Fanny Price is sent to live with her wealthy uncle and aunt, Sir Thomas and Lady Bertram at Mansfield Park. Raised among her four cousins, Fanny, the poor relation, often goes unobserved in the household, making her a unique observer of the ethics, morals, attitudes and behavior of English society.